Comparative Analysis of Subventricular Zone Glioblastoma Contact and Ventricular Entry During Resection in Predicting Dissemination, Hydrocephalus, and Survival. Issue 5 (6th May 2019) - Mistry, Akshitkumar M; Kelly, Patrick D; Gallant, Jean-Nicolas; Mummareddy, Nishit; Mobley, Bret C; Thompson, Reid C; Chambless, Lola B
Abstract: BACKGROUND: Ventricular entry during glioblastoma resection and tumor contact with the subventricular zone (SVZ) have both been shown to associate with development of hydrocephalus, leptomeningeal dissemination, distant parenchymal recurrence, and decreased survival. However, prior studies did not analyze these variables together in a single-patient population; therefore, it is unknown which is an independent predictor of these outcomes. OBJECTIVE: To conduct a comparative outcome analysis of surgical ventricular entry and SVZ contact by glioblastoma in a retrospective cohort of 232 patients. METHODS: Outcomes studied included hydrocephalus, leptomeningeal dissemination, distant tumor recurrences, and progression-free (PFS) and overall (OS) survival. The Cox proportional regression analyses were adjusted for age at diagnosis, preoperative Karnofsky performance status score, extent of resection, temozolomide and radiation treatments, and tumor molecular status (specifically, IDH1/2 mutation and MGMT promoter methylation). RESULTS: Surgical ventricular entry, SVZ-contacting glioblastoma, hydrocephalus, leptomeningeal dissemination, and distant recurrences were observed in 85 (36.6%), 114 (49.1%), 19 (8.2%), 78 (33.6%), and 59 (25.4%) patients, respectively. Multivariate, adjusted analysis revealed SVZ tumor contact—but not ventricular entry—associated with hydrocephalus (hazard ratio, HR, 4.20 [1.13-15.7], P  = .03), leptomeningeal dissemination (HR 1.93 [1.14-3.28], P  = .01), PFS (HR 2.10 [1.53-2.88], P  < .001), and OS (HR 1.90 [1.35-2.67], P  < .001). Distant recurrences were not associated with either. No interaction between the 2 variables was statistically noted. CONCLUSION: SVZ contact by glioblastoma was independently associated with the development of hydrocephalus, leptomeningeal dissemination, and decreased survival. SVZ tumor contact was associated with ventricular entry during surgical resections, which did not independently correlate with these outcomes.